The Effect of Pyraclostrobin Application on Yield of Tea (Camelia sinensis (L.) O. Kuntze) under Wet Season - Arief Rahman; Eka Tarwaca Susila Putra; Sriyanto Waluyo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
This field experiment aimed to study the effect of pyraclostrobin on tea production and to determine optimum concentration in order to maintain high yield during the period of wet season. The experiment was arranged in Randomized Completely Block Design (RCBD) using single factor and three blocks as replications. The pyraclostrobin doses, consisted of 4 levels, 0, 50, 100, and 150 g.ha-1, each will be tested on three tea clones. Clones tea tested are TRI 2025, Gambung 9 and PGL 15. Data was evaluated for chlorophyll content, photosynthetic rate, number of pecco, number of dormant shoot (banjhi), number of total shoot, pecco fresh weight, banjhi fresh weight, total shoot fresh weight, and shoot dry weight. Data were analysed by using Analysis of Variance (ANOVA) and LSD test at α = 5%. The results informed that pyraclostrobin was able to improve chlorophyll content on TRI 2025 clone, and improved photosynthetic rate on Gambung 9 clone. However, there was no significant different among plants treated with pyraclostrobin on a yield components, i.e., number of pecco, number of banjhi, pecco fresh weight, banjhi fresh weight, total shoot fresh weight, and total shoot dry weight.